Anti-Rods/Rings: A Human Model of Drug-Induced Autoantibody Generation - Calise, S. John; Keppeke, Gerson D.; Andrade, Luis E. C.; Chan, Edward K. L. (Frontiers in Immunology, 2015)
In recent years, autoantibodies targeting subcellular structures described as the rods and rings pattern in HEp-2 ANA have been presented as a unique case of autoantibody generation. These rod and ring structures (RR) are at least partially composed of inosine monophosphate dehydrogenase type 2 (IMPDH2), and their formation can be induced in vitro by several small-molecule inhibitors, including some IMPDH2 inhibitors. Autoantibodies targeting these relatively unknown structures have been almost exclusively observed in hepatitis C (HCV) patients who have undergone treatment with pegylated interferon-α/ribavirin (IFN/RBV) combination therapy. To date, anti-RR antibodies have not been found in treatment-naïve HCV patients or in patients from any other disease groups, with few reported exceptions. Here, we describe recent advances in characterizing the RR structure and the strong association between anti-RR antibody response and HCV patients treated with IFN/RBV, detailing why anti-RR can be considered a human model of drug-induced autoantibody generation.